Evaluating socio-economic and environmental factors influencing farm-level water scarcity in Punjab, Pakistan - Khan, Muhammad Awais Ali; Mahmood Ch., Khalid; Ashraf, Ijaz; Siddiqui, Muhammad Tahir; Knox, Jerry W. (Wiley, 2020)
Pakistan's economy is primarily dependent on agriculture, but it faces serious water challenges. This paper critically evaluates the water resources and socio‐economic and environmental factors contributing to increased farm‐level water scarcity in the Punjab region. The study involved conducting structured interviews with 370 farmers to gather data necessary for conducting a detailed sociotechnical factor analysis. From this, eight factors were identified that were found to directly impact farmer well‐being including climate change (rise in temperature and erratic rainfall), poor socio‐economic farmer conditions, issues linked to the warabandi (canal water distribution system), inadequate irrigation, reduced water availability, poor water course maintenance, and low adoption of efficient irrigation techniques. The Kruskal‐Wallis test was then used to assess statistical differences between the respondents' demographic attributes and the identified factors. Demographic factors including age, education, land size, farming experience, and cultivated area showed significant mean differences with the eight factors. Young farmers with higher education levels were more likely to adopt high‐efficiency irrigation systems to conserve water. The research also highlighted the importance of introducing crops with a lower water demand into the region and the need to proactively support agricultural extension services to encourage farmers to adopt more efficient irrigation systems to improve crop productivity and facilitate on‐farm water conservation.
Keywords: water resources; irrigation; drought; climate change; agriculture